2020
DOI: 10.1186/s13059-020-02106-z
|View full text |Cite
|
Sign up to set email alerts
|

Insulator-based loops mediate the spreading of H3K27me3 over distant micro-domains repressing euchromatin genes

Abstract: Background: Chromosomes are subdivided spatially to delimit long-range interactions into topologically associating domains (TADs). TADs are often flanked by chromatin insulators and transcription units that may participate in such demarcation. Remarkably, single-cell Drosophila TAD units correspond to dynamic heterochromatin nanocompartments that can self-assemble. The influence of insulators on such dynamic compartmentalization remains unclear. Moreover, to what extent heterochromatin domains are fully compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 82 publications
(189 reference statements)
3
24
0
Order By: Relevance
“…This would be notably consistent with the previously described role of Mod(mdg4) in organizing 3D contacts between regulatory elements and promoters [36]. It would also be consistent with recent findings that H3K27me3 micro-domains may reflect such contacts [53].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This would be notably consistent with the previously described role of Mod(mdg4) in organizing 3D contacts between regulatory elements and promoters [36]. It would also be consistent with recent findings that H3K27me3 micro-domains may reflect such contacts [53].…”
Section: Discussionsupporting
confidence: 92%
“…This would be notably consistent with the previously described role of Mod(mdg4) in organizing 3D contacts between regulatory elements and promoters [36]. It would also be consistent with recent findings that H3K27me3 micro-domains may reflect such contacts [53]. However, no interaction between dhd and any other locus can be found in Hi-C data, and our rescue transgene experiments show that a small (4kb), ectopic genomic segment encapsulates the elements required for ovary-specific hyperactivation, arguing against a critical role of the genomic and epigenomic environment in the dhd locus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Heatmaps on genomic features were created using genomation’s ( 41 ) gridHeat function, using the profile matrices generated by DeepTools. GSEA was performed using fgsea as described previously ( 42 ), and all enrichment plots were created using the plotEnrichment function of the package. Decile matrices were created using color2D matplot from the plotrix package.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study showed that HP1c and HP1b form heterodimers in vitro and in vivo 42 . (D) Previously published studies showed that BEAF-32 regulates the expression of genes not directly bound by BEAF-32 through long-range contacts that depend on the interaction of BEAF-32 with CP190 10,43 .…”
Section: Discussionmentioning
confidence: 99%